Multi-stage process for producing ethylene-based polymers with (ultra) high molecular weight polyethylene components

By producing UHMWPE in solution at low to medium reaction temperatures and blending with ethylene-based polymers under subsequent solution processing conditions, the problem of difficulty in binding UHMWPE with ethylene-based polymers in the prior art is solved, and better polymer binding and performance improvement is achieved.

CN119894946APending Publication Date: 2025-04-25DOW GLOBAL TECHNOLOGIES LLC
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202380065460.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-26
Filing Date
2023-09-26
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The prior art is difficult to effectively bind ultra-high molecular weight polyethylene (UHMWPE) to ethylene-based polymers (such as LLDPE), resulting in difficulty in binding these entangled UHMWPE clusters in the molecular structure of the polymer.

Method used

UHMWPE is produced in solution at low to medium reaction temperatures, and the catalyst used is intended to produce UHMWPE chains dissolved in the solvent or evenly dispersed as fine mist, thereby blending with ethylene-based polymer solutions under subsequent solution processing conditions to achieve highly detangled UHMWPE fractions.

Benefits of technology

By this method, UHMWPE can be better combined in ethylene-based polymers, improving the toughness and processability of the polymer and reducing the relative size of UHMWPE particles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005307718390000121
    Figure BDA0005307718390000121
  • Figure BDA0005307718390000131
    Figure BDA0005307718390000131
  • Figure BDA0005307718390000132
    Figure BDA0005307718390000132
Patent Text Reader

Abstract

An embodiment of a process for producing an ethylene-based polymer comprising a first polymer fraction and a second polymer fraction comprises: reacting an ethylene monomer and optionally a C3-C12 alpha-olefin comonomer in a solvent in the presence of a first catalyst in at least one initial reactor, the first polymer fraction has a weight average molecular weight (Mw) of greater than 500,000 g / mol to produce the first polymer fraction that reaches an outlet temperature of the reaction zone of less than 160 DEG C, where the first polymer fraction has a weight average molecular weight (Mw) of greater than 500,000 g / mol; introducing the first polymer fraction, the ethylene monomer, the optional C3-C12 alpha-olefin comonomer, the solvent, at least one second catalyst to at least one stirred solution polymerization reactor; and reacting the ethylene monomer and the optional C3-C12 alpha-olefin comonomer in a solvent in the at least one stirred solution polymerization reactor in the presence of the at least one second catalyst to produce a second polymer fraction.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of U.S. Provisional Application Serial No. 63 / 409,941, filed on September 26, 2022, the entire disclosure of which is hereby incorporated by reference into this document. Technical Field

[0003] The present specification generally relates to processes for making ethylene-based polymers, and in particular to methods for making ethylene-based polymers comprising an ultra-high molecular weight component. Background Art

[0004] In order to improve the toughness and processability of ethylene-based polymers (e.g., LLDPE), (ultra) high molecular weight polyethylene (UHWMPE) materials can be added to ethylene-based polymers. At present, UHMWPE is produced in slurry phase or gas phase using heterogeneous catalysts. Conventionally, adding UHMWPE via blending leads to relatively large UHMWPE particles, which are composed of highly entangled macromolecules. Due to extreme viscosity differences, it is difficult to combine these entangled UHMWPE clusters in the molecular structure of ethylene-based polymers. Specifically, the melt index (I2) of UHMWPE can be less than 0.01, while the bulk resin (e.g., LLDPE) can have a melt index at least one hundred times greater than the melt index. Therefore, there is a continuous need to better combine UHMWPE in a method based on ethylene-based polymers (such as LLDPE). Summary of the invention

[0005] Embodiments of the present disclosure meet this need for improved UHMWPE incorporation by producing UHMWPE in solution at low to moderate reaction temperatures, where the catalyst used is not for particle formation (as in slurry phase or gas phase technology), but is intended to produce UHMWPE chains that are dissolved in a solvent or uniformly dispersed as a fine mist (very fine phase separation). Under subsequent solution processing conditions, the dissolved or dispersed UHMWPE will be blended with an ethylene-based polymer solution. This results in a highly disentangled UHMWPE fraction in solution that is easily incorporated in a downstream solution reactor for producing ethylene-based polymers.

[0006] According to one embodiment, a method for producing an ethylene-based polymer comprising a first polymer fraction and a second polymer fraction is provided. The method comprises: reacting ethylene monomer and optionally C3-C 12The α-olefin comonomer is reacted in at least one initial reactor in the presence of a first catalyst in a solvent to produce the first polymer fraction reaching an outlet temperature of the reaction zone below 160° C., wherein the weight average molecular weight (Mw) of the first polymer fraction is greater than 500,000 g / mol; the first polymer fraction, the ethylene monomer, the optional C3-C 12 α-olefin comonomer, the solvent, at least one second catalyst are introduced into at least one stirred solution polymerization reactor; the ethylene monomer and the optional C3-C 12 The method comprises reacting an α-olefin comonomer in the presence of the at least one second catalyst in the at least one stirred solution polymerization reactor to produce a second polymer fraction; and outputting an effluent from the stirred solution polymerization reactor, wherein the effluent comprises the ethylene-based polymer having the first polymer fraction and the second polymer fraction, unreacted ethylene monomer, and optionally unreacted C3-C 12 The ethylene-based polymer comprises 0.1 wt % to 15 wt % of the first polymer fraction and greater than 70 wt % of the second polymer fraction. In addition, the ethylene-based polymer has a melt index (I2) of 0.1 g / 10 min to 50 g / 10 min, a density of 0.870 g / cc to 0.970 g / cc, and Mz / Mw is greater than Mw / Mn.

[0007] Additional features and advantages will be set forth in the following Detailed Description, and in part will become apparent to those skilled in the art from that description or may be learned by practicing the embodiments described herein, including the drawings, the following Detailed Description, and the claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0008] Figure 1 is a schematic diagram of the process of the present invention according to one or more embodiments of the present disclosure;

[0009] Figure 2 is another schematic diagram of the process of the present invention according to one or more embodiments of the present disclosure;

[0010] Figure 3 is yet another schematic diagram of the process of the present invention according to one or more embodiments of the present disclosure;

[0011] Figure 4 is an experimental sample according to one or more embodiments of the present disclosure 10 / I2 versus I2 plot;

[0012] Figure 5 is a graph of melt strength versus dynamic melt viscosity for experimental samples according to one or more embodiments of the present disclosure; and

[0013] Fig. 6A and Figure 6B is a graph of uniaxial stress growth coefficient versus time for experimental samples according to one or more embodiments of the present disclosure. DETAILED DESCRIPTION

[0014] The specific embodiments of the application will now be described. However, the present disclosure can be implemented in different forms and should not be construed as being limited to the embodiments set forth in the present disclosure. On the contrary, these embodiments are provided so that the present disclosure will be thorough and complete, and will fully convey the scope of the subject matter to those skilled in the art.

[0015] definition

[0016] The term "polymer" refers to a polymeric compound prepared by polymerizing monomers (whether of the same or different types). Thus, the general term polymer encompasses the term "homopolymer," which is generally used to refer to polymers prepared from only one type of monomer, and "copolymer," which refers to polymers prepared from two or more different monomers. The term "interpolymer," as used herein, refers to a polymer prepared by the polymerization of at least two different types of monomers. Thus, the general term interpolymer includes copolymers and polymers prepared from more than two different types of monomers (such as terpolymers).

[0017] "Polyethylene" or "ethylene-based polymer" shall mean a polymer comprising greater than 50% by weight of units that have been derived from ethylene monomers. This includes polyethylene homopolymers or copolymers (meaning units derived from two or more comonomers). Comonomers may include olefin comonomers as well as polar comonomers. Common forms of polyethylene known in the art include low density polyethylene (LDPE); linear low density polyethylene (LLDPE); ultra low density polyethylene (ULDPE); very low density polyethylene (VLDPE); single-site catalyzed linear low density polyethylene, including both linear low density resins and substantially linear low density resins (m-LLDPE); medium density polyethylene (MDPE); and high density polyethylene (HDPE).

[0018] The term "LDPE" may also be referred to as "high pressure ethylene polymer" or "highly branched polyethylene" and is defined to mean a polymer partially or completely homopolymerized or copolymerized in an autoclave or tubular reactor at pressures above 14,500 psi (100 MPa) by using a free radical initiator such as a peroxide (see, e.g., U.S. Pat. No. 4,599,392, which is incorporated herein by reference). The density of LDPE resins is typically in the range of 0.916 grams per cubic centimeter (g / cc) to 0.935 g / cc.

[0019] The term "LLDPE" includes resins made using a Ziegler-Natta catalyst system, as well as resins made using single-site catalysts, including but not limited to dual metallocene catalysts (sometimes referred to as "m-LLDPE") and constrained geometry catalysts; and resins made using post-metallocene and molecular catalysts. LLDPE includes linear, substantially linear or heterogeneous polyethylene copolymers or homopolymers. Compared to LDPE, LLDPE contains less long chain branching and includes substantially linear ethylene polymers, which are further defined in U.S. Pat. No. 5,272,236, U.S. Pat. No. 5,278,272, U.S. Pat. No. 5,582,923, and U.S. Pat. No. 5,733,155; homogeneously branched linear ethylene polymer compositions, such as those in U.S. Pat. No. 3,645,992; heterogeneously branched ethylene polymers, such as those prepared according to the process disclosed in U.S. Pat. No. 4,076,698; and / or blends thereof (such as those disclosed in U.S. Pat. No. 3,914,342 or U.S. Pat. No. 5,854,045). LLDPE resins can be prepared via gas phase, solution phase, or slurry polymerization, or any combination thereof, using any type of reactor or reactor configuration known in the art.

[0020] The term "MDPE" refers to polyethylene having a density of 0.926 g / cc to 0.940 g / cc. "MDPE" is typically produced using chromium or Ziegler-Natta catalysts or using single site catalysts including but not limited to dual metallocene catalysts and constrained geometry catalysts.

[0021] The term "HDPE" refers to polyethylene having a density greater than about 0.940 g / cc, which is typically produced using Ziegler-Natta catalysts, chromium catalysts, or single site catalysts including but not limited to dual metallocene catalysts and constrained geometry catalysts.

[0022] The term "UHMWPE" refers to polyethylene having a weight average molecular weight (Mw) greater than 500,000 g / mol as measured according to conventional gel permeation chromatography.

[0023] The term "disentangled network" refers to a polymer in which the chains are less interconnected, thereby allowing increased fluidity, processability and stretchability. Conversely, the term "entangled network" refers to a polymer in which the chains are highly interconnected, thereby reducing fluidity, processability and stretchability.

[0024] As used in the present disclosure, the term "blend" or "polymer blend" as used refers to a mixture of two or more polymers. Blends may be miscible or may be immiscible (not phase separated at the molecular level). Blends may or may not be phase separated. Blends may or may not contain one or more domain configurations, as determined by transmission electron spectroscopy, light scattering, x-ray scattering, and other methods known in the art. Blends can be prepared by physically mixing two or more polymers at the macroscopic level (e.g., melt blending resins or compounding) or at the microscopic level (e.g., simultaneously formed in the same reactor). Blends can be prepared in the melt phase or by solution blending in a common solvent.

[0025] The terms "comprising," "including," "having," and derivatives thereof are not intended to exclude the presence of any additional components, steps, or procedures, whether or not specifically disclosed. For the avoidance of any doubt, all compositions claimed through use of the term "comprising" may include any additional additives, adjuvants, or compounds, whether polymeric or otherwise, unless stated to the contrary. In contrast, the term "consisting essentially of excludes from the scope of any subsequently recited any other components, steps, or procedures, except those that are not essential to operability. The term "consisting of excludes any component, step, or procedure not specifically recited or listed.

[0026] Embodiments of the present disclosure are directed to systems and methods for producing ethylene-based polymers comprising a first polymer fraction and a second polymer fraction. The first polymer fraction may also be referred to herein as a high molecular weight fraction or "HMW fraction," while the second polymer fraction may also be referred to herein as a "bulk fraction." Reference Figures 1 to 3 The method comprises: making ethylene monomer and optionally C3-C 12 The α-olefin comonomer is reacted in the presence of a first catalyst 20 in a solvent 10 in at least one initial reactor 100 to produce a first polymer fraction 130 reaching an outlet temperature of less than 160° C. from the reaction zone, wherein the weight average molecular weight (Mw) of the first polymer fraction is greater than 500,000 g / mol. The first polymer fraction may also be considered a UHMWPE fraction. Various means for supplying monomers, solvents, and catalysts are considered suitable. In the case of Figure 2 In another embodiment shown, ethylene 2, C3-C 12 The α-olefin comonomer 4 and the solvent 6 may be mixed in a mixing vessel 50 upstream of the initial reactor 100. Figure 2Mixing vessel 50 is depicted as a continuous stirred tank reactor (CSTR), but various additional mixing vessels are considered suitable. Figure 2 As shown, the main catalyst 22 and the co-catalyst 24 can be fed separately as shown, or as shown in FIG. Figure 1 As shown, the catalyst may be fed in a single stream 20 .

[0027] In one or more embodiments, the initial reactor 100 may include a tubular reactor, such as a tubular plug flow reactor. In addition, as described above, the outlet temperature may be less than 160°C or less than 157°C. In addition, the outlet temperature may be 60°C to 160°C, or 60°C to 90°C, or 80°C to 110°C, or 120°C to 160°C, or 120°C to 145°C, or 130°C to 155°C, 140°C to 160°C. The pressure range may be from about 400psi to about 1000psi, or from about 650psi to about 800psi. The residence time may be from about 0.5 minutes to about 15 minutes, or from about 0.5 minutes to about 2 minutes. In other embodiments, the initial reactor (such as a tubular reactor) may be operated under adiabatic conditions. In other embodiments, the initial reactor (such as a tubular reactor) may be operated using cooling, heating, or a combination thereof.

[0028] Various solvents are considered suitable. Exemplary solvents include, but are not limited to, isoparaffins. For example, such solvents are commercially available under the name ISOPAR E (ExxonMobil Chemical Co., Houston, Tex.).

[0029] In the first fraction, ethylene monomer may be present in an amount of at least 50 wt%, or at least 60 wt%, or at least 70 wt%, or at least 80 wt%. 12 The α-olefin comonomer may be present in the first fraction in an amount less than 50 weight percent, or less than 40 weight percent, or less than 30 weight percent, or less than 20 weight percent.

[0030] The first catalyst may include at least one molecular catalyst, at least one heterogeneous Ziegler-Natta catalyst, or a combination thereof. It is also contemplated that constrained geometry and metallocene catalysts are suitable. In one embodiment, the first catalyst includes a molecular catalyst. The molecular catalyst may include one or more bis-biphenyl-phenoxy catalysts. Without being bound by theory, the use of a molecular homogeneous catalyst in a temperature range below 160° C. helps to produce a first fraction of UHMWPE in a phase separation mode that can be better combined in a second polymer fraction produced in a downstream stirred solution polymerization reaction, as further defined below. In addition, without being bound by theory, the restricted crystallization of these UHMWPE chains gives the potential to change the performance characteristics of the entire polymer.

[0031] The first polymer fraction can comprise a weight average molecular weight (Mw) greater than 500,000 g / mol, greater than 750,000 g / mol, or greater than 1,000,000 g / mol as measured according to gel permeation chromatography. Additionally, the first polymer fraction can comprise an Mw of 500,000 g / mol to 1,500,000 g / mol, 500,000 g / mol to 1,250,000 g / mol, 500,000 g / mol to 1,100,000 g / mol, 750,000 g / mol to 1,500,000 g / mol, 750,000 g / mol to 1,250,000 g / mol, 750,000 g / mol to 1,100,000 g / mol, 900,000 g / mol to 1,500,000 g / mol, 900,000 g / mol to 1,200,000 g / mol, or 900,000 g / mol to 1,100,000 g / mol. In addition, the first polymer fraction may comprise a number average molecular weight (Mn) of greater than 250,000 g / mol, or greater than 400,000 g / mol, or greater than 500,000 g / mol as measured according to gel permeation chromatography. Additionally, the first polymer fraction may comprise an Mn of 250,000 g / mol to 750,000 g / mol, 250,000 g / mol to 600,000 g / mol, 400,000 g / mol to 750,000 g / mol, or 400,000 g / mol to 600,000 g / mol. In addition, the first polymer fraction may have a MWD (=Mw / Mn) of 1 to 20, 1 to 15, 1 to 10, 1 to 5, or 1 to 3.

[0032] In addition, the density of the first polymer fraction can be in the range of 0.870 g / cc to 0.920 g / cc, 0.870 g / cc to 0.900 g / cc, or 0.870 g / cc to 0.890 g / cc. The melt index (I2) can be in the range of 0.0001 dg / min to 0.5 dg / min, 0.0001 dg / min to 0.1 dg / min, or 0.0001 dg / min to 0.05 dg / min.

[0033] refer to Figures 1 to 3 The first polymer fraction 130, the ethylene monomer 110, the optional C3-C 12 The α-olefin comonomer 120, solvent and optionally at least one second catalyst 140 are fed to at least one stirred solution polymerization reactor 200. In the stirred solution polymerization reactor 200, ethylene monomer and optionally C3-C 12 The alpha-olefin comonomer is reacted in a solvent in the presence of a second catalyst to produce a second polymer fraction.

[0034] In one or more embodiments, the stirred solution polymerization reactor 200 may include at least one continuous stirred tank reactor (CSTR), at least one loop reactor, or a combination thereof. In addition, as described above, the outlet temperature may be from about 150°C to about 575°C, or from about 175°C to about 205°C. The pressure range may be from about 30psi to about 1000psi, or from about 30psi to about 750psi. The residence time may be from about 2 minutes to about 20 minutes, or from about 10 minutes to about 20 minutes. In additional embodiments, the CSTR or loop reactor outlet is connected to a tubular post reactor that may reach an outlet temperature greater than 205°C.

[0035] Similar to the upstream initial reactor, various solvents are considered suitable. Exemplary solvents include, but are not limited to, isoparaffins, such as ISOPAR E. In one or more embodiments, the fraction of the first polymer in the stirred solution polymerization reactor 200 can be less than 5 wt%, less than 2 wt%, less than 1 wt%.

[0036] In the second polymer fraction, the ethylene monomer may be present in an amount of at least 50 wt%, or at least 60 wt%, or at least 70 wt%, or at least 80 wt%. 12 The alpha-olefin comonomer may be present in the second fraction in an amount less than 50 wt%, or less than 40 wt%, or less than 30 wt%, or less than 20 wt%.In one or more embodiments, the second polymer fraction comprises LLDPE.

[0037] Various compositions are considered suitable for the second catalyst. In one embodiment, the first catalyst and the second catalyst comprise different compositions. In other embodiments, the second catalyst may include at least one molecular catalyst, at least one heterogeneous Ziegler-Natta catalyst, or a combination thereof. It is also contemplated that constrained geometry and metallocene catalysts are suitable. In another embodiment, the second catalyst may include a heterogeneous Ziegler-Natta catalyst.

[0038] The second polymer fraction may comprise a weight average molecular weight (Mw) of greater than 50,000 g / mol, greater than 75,000 g / mol, or greater than 90,000 g / mol as measured by gel permeation chromatography. Additionally, the second polymer fraction may comprise a Mw of 50,000 g / mol to 120,000 g / mol, 50,000 g / mol to 100,000 g / mol, 75,000 g / mol to 120,000 g / mol, 75,000 g / mol to 100,000 g / mol, or 90,000 g / mol to 120,000 g / mol, 90,000 g / mol to 100,000 g / mol. In addition, the second polymer fraction may comprise a number average molecular weight (Mn) of greater than 10,000 g / mol, or greater than 15,000 g / mol as measured by gel permeation chromatography. Additionally, the second polymer fraction may comprise an Mn of 10,000 g / mol to 50,000 g / mol, 10,000 g / mol to 25,000 g / mol, 15,000 g / mol to 50,000 g / mol, or 15,000 g / mol to 25,000 g / mol. Furthermore, the second polymer fraction may have an MWD (=Mw / Mn) of 1 to 20, 1 to 15, 1 to 10, 2 to 5, or 3 to 5.

[0039] In addition, the density of the second polymer fraction can be in the range of 0.870 g / cc to 0.970 g / cc, 0.870 g / cc to 0.940 g / cc, 0.890 g / cc to 0.920 g / cc, or 0.905 g / cc to 0.920 g / cc. The melt index (I2) can be in the range of 0.1 dg / min to 50 dg / min, 0.1 dg / min to 5 dg / min, 1 dg / min to 5 dg / min, or 1 dg / min to 3 dg / min.

[0040] Reference again Figures 1 to 3 The effluent 210 output from the stirred solution polymerization reactor 200 may include the first polymer fraction and the second polymer fraction, unreacted ethylene monomer and optionally unreacted C3-C 12α-olefin comonomer. The ethylene-based polymer comprises 0.1 wt % to 15 wt % of a first polymer fraction and greater than 70 wt % of a second polymer fraction. In addition, the ethylene-based polymer has a melt index (I2) of 0.1 g / 10 min to 50 g / 10 min, a density of 0.870 g / cc to 0.970 g / cc, and Mz / Mw is greater than Mw / Mn.

[0041] In embodiments, the effluent from stirred solution polymerization reactor 200 may be subjected to one or more separation steps to separate unreacted ethylene monomer and optionally unreacted C3-C 12 Ethylene-based polymers are isolated from the alpha-olefin comonomers.

[0042] Ethylene-based polymers may include a weight average molecular weight (Mw) greater than 50,000 g / mol, greater than 50,000 g / mol, or greater than 100,000 g / mol as measured by gel permeation chromatography. Additionally, ethylene-based polymers may include a Mw of 50,000 g / mol to 150,000 g / mol, 50,000 g / mol to 120,000 g / mol, 75,000 g / mol to 150,000 g / mol, 75,000 g / mol to 120,000 g / mol, 90,000 g / mol to 150,000 g / mol, or 90,000 g / mol to 120,000 g / mol. In addition, ethylene-based polymers may include a number average molecular weight (Mn) greater than 10,000 g / mol, or greater than 15,000 g / mol as measured by gel permeation chromatography. In addition, the polymer based on ethylene can include 10,000g / mol to 50,000g / mol, 10,000g / mol to 25,000g / mol, 15,000g / mol to 50,000g / mol, or 15,000g / mol to 25,000g / mol Mn. The polymer based on ethylene can include at least 500,000g / mol, or 750,000g / mol z-average molecular weight (Mz). The polymer based on ethylene can include 750,000g / mol to 1,000,000g / mol, or 800,000g / mol to 900,000g / mol Mz. In addition, the polymer based on ethylene can have 1 to 20, 1 to 15, 1 to 10, 5 to 10, or 5 to 7 Mz / Mw.

[0043] In addition, the density of the ethylene-based polymer can be in the range of 0.870 g / cc to 0.970 g / cc, 0.870 g / cc to 0.940 g / cc, 0.890 g / cc to 0.920 g / cc, or 0.905 g / cc to 0.920 g / cc. The melt index (I2) can be in the range of 0.1 dg / min to 50 dg / min, 0.1 dg / min to 25 dg / min, 0.1 dg / min to 10 dg / min, 0.1 dg / min to 5 dg / min, 0.5 dg / min to 50 dg / min, 0.5 dg / min to 25 dg / min, 0.5 dg / min to 5 dg / min, 0.5 dg / min to 2 dg / min, or 0.5 dg / min to 1 dg / min. The ethylene-based polymer may have an I of 1 to 30, 5 to 20, 5 to 15, 9 to 15, or 9 to 12. 10 / I2.

[0044] Alternatively, if Figure 2 and Figure 3 As shown, the effluent 210 of the stirred solution polymerization reactor 200 can be sent to a mixer 300 downstream of the stirred solution polymerization reactor 200, wherein the mixer includes the addition of a third catalyst 220. The third catalyst promotes the removal of unreacted ethylene monomer and optionally any unreacted C3-C 12 Further reaction of the alpha-olefin comonomer to produce a third polymer fraction having a density and a melt index (I2) different from the second polymer fraction.

[0045] The third catalyst includes at least one molecular catalyst, at least one heterogeneous Ziegler-Natta catalyst, or a combination thereof. It is also contemplated that constrained geometry and metallocene catalysts are suitable.

[0046] exist Figure 3 In another embodiment shown, the method includes introducing a mixer effluent 310 from a mixer 300 into a tubular polymerization reactor 400, wherein the mixer effluent 310 comprises an ethylene-based polymer having a first polymer fraction, a second polymer fraction, and a third polymer fraction. Although the third catalyst 220 may have been fed in the upstream mixer 300, it is contemplated that the third catalyst or another catalyst may be added to the tubular reactor 300, as shown by stream 320.

[0047] Ethylene-based polymers are considered to be suitable for a variety of applications. For example, they are considered to be suitable for films (single and multilayer), fibers, nonwovens, artificial turf, and various articles incorporating these films. For example, ethylene-based polymers can be used for various films, including but not limited to extrusion coatings, food packaging, consumer products, industry, agriculture (applications or films), laminated films, fresh-cut manufacturing films, meat films, cheese films, candy films, clear shrink films, collation shrink films, stretch films, oriented films (MDO, BOPE), silage films, greenhouse films, fumigation films, liner films, stretch hoods, heavy-duty shipping bags, pet food, sandwich bags, sealants, and diaper backsheets.

[0048] Test Method

[0049] density

[0050] Samples for density measurements were prepared according to ASTM D 1928. Polymer samples were pressed at 190°C and 30,000 psi for three minutes, then at 21°C and 207 MPa for one minute. Measurements were made using ASTM D792, Method B within one hour of sample pressing.

[0051] Melt index (I2)

[0052] Melt index or I2 (grams / 10 minutes or dg / min) is measured according to ASTM D 1238, Condition 190°C / 2.16 kg, Procedure B.

[0053] Melt Strength

[0054] Melt strength was measured at 190°C using a Goettfert Rheotens 71.97 (Goettfert Inc.; Rock Hill, SC) with the melt fed using a Goettfert Rheotester 2000 capillary rheometer equipped with a flat inlet angle (180 degrees) of 30 mm in length and 2 mm in diameter. The pellets were fed into a barrel (L = 300 mm, diameter = 12 mm), compressed and allowed to melt for 10 minutes, and then extruded at a constant piston speed of 0.265 mm / s, which corresponds to 38.2 s at a given die diameter. -1 The extrudate passes through a Rheotens wheel located 100 mm below the die exit and is sheared at 2.4 mm / s by the wheel. 2 The force applied to the wheel (in cN) is recorded as a function of wheel speed (mm / s). The melt strength is reported as the plateau force (cN) before strand breakage or significant pull resonance.

[0055] Dynamic-Mechanical Spectroscopy (DMS)

[0056] Melt rheology at constant temperature, frequency sweep, was performed using a TA Instruments Advanced Rheology Extension System (ARES) rheometer equipped with 25 mm parallel plates under nitrogen purge. The frequency sweep was performed at 190°C with a constant tension of 10% for all samples separated by 2.0 mm. The frequency range was 0.1 rad / sec to 100 rad / sec. The stress response was analyzed in terms of amplitude and phase, from which the storage modulus (G'), loss modulus (G), and dynamic melt viscosity (n*) were calculated.

[0057] Triple Detector Gel Permeation Chromatography (TDGPC)

[0058] The chromatographic system consisted of a PolymerChar GPC-IR (Valencia, Spain) high temperature GPC chromatograph equipped with an internal IR5 infrared detector (IR5) and 4 capillary viscometers (DV) connected to a Precision Detectors (now Agilent Technologies) 2-angle laser scattering (LS) detector model 2040. For all light scattering measurements, a 15 degree angle was used for measurement purposes. The autosampler oven chamber was set to 160 degrees Celsius, and the column chamber was set to 150 degrees Celsius. The columns used were 4 Agilent "Mixed A" 30 cm 20 micron linear mixed bed columns and 20um pre-columns. The chromatographic solvent used was 1,2,4 trichlorobenzene and contained 200 ppm of butylated hydroxytoluene (BHT). The solvent source was nitrogen sparged. The injection volume used was 200 microliters, and the flow rate was 1.0 ml / min.

[0059] Calibration and calculation of conventional molecular weight moments and distributions were performed according to methods described in conventional GPC procedures (using a 20 um "Mixed A" column).

[0060] A systematic approach for determining multi-detector shifts was developed in accordance with Balke, Mourey et al. (Mourey and Balke, Chromatography Polym., Chapter 12, (1992)) (Balke, Thitiratsakul, Lew, Cheung, Mourey, Chromatography Polym., Chapter 13, (1992)) using the PolymerChar GPCOne TMThe software optimizes the triple detector log (MW and IV) results from broad homopolymer polyethylene standards (Mw / Mn>3) with the narrow standards column calibration results from the narrow standards calibration curve.As used herein, "MW" refers to molecular weight.

[0061] Absolute molecular weight data using PolymerChar GPCOne TM The software was obtained in a manner consistent with that published by Zimm (Zimm, BH, Chem. Phys., 16, 1099 (1948)) and Kratochvil (Kratochvil, P., Classical Light Scattering from Polymer Solutions, Elsevier, Oxford, NY (1987)). The total injected concentration used to determine the molecular weight is obtained from the mass detector area and the mass detector constant, which is derived from a suitable linear polyethylene homopolymer or one of the polyethylene standards of known weight average molecular weight. The calculated molecular weight (using GPCOne TM ) is obtained using the light scattering constants from one or more of the polyethylene standards mentioned below and a refractive index concentration coefficient dn / dc of 0.104. Typically, the mass detector response (IR5) and the light scattering constant (using GPCOne TM Viscometer calibration (using GPCOne TM The viscometer constant (measured using GPCOne TM The specific viscosity area (DV) and injected mass of the calibration standard are related to its intrinsic viscosity (IV). The chromatographic concentration is assumed to be low enough to eliminate the effect of the 2nd Virial coefficient (the effect of concentration on molecular weight).

[0062] The absolute weight average molecular weight (Mw(Abs)) is calculated by dividing the light scattering (LS) integrated chromatogram (determined by the light scattering constant) by the mass recovered from the mass constant and mass detector (IR5) area (using GPCOne TM ). Molecular weight and intrinsic viscosity responses were extrapolated at the end of the chromatogram where the signal-to-noise ratio becomes low (using GPCOne TM ). Other corresponding moments Mn (Abs) and Mz (Abs) The calculation according to equation 1-2 is as follows:

[0063]

[0064] For conventional GPC: The chromatographic system consisted of a PolymerChar GPC-IR (Valencia, Spain) high temperature GPC chromatograph equipped with an internal IR5 infrared detector (IR5) coupled to a Precision Detector (now Agilent Technologies) 2-angle laser light scattering (LS) detector model 2040. For all light scattering measurements, a 15 degree angle was used for measurement purposes. The autosampler oven chamber was set to 160 degrees Celsius and the column chamber was set to 150 degrees Celsius. The columns used were 4 Agilent "Mixed A" 30 cm 20 micron linear mixed bed columns. The chromatographic solvent used was 1,2,4 trichlorobenzene and contained 200 ppm of butylated hydroxytoluene (BHT). The solvent source was nitrogen sparged. The injection volume used was 200 microliters and the flow rate was 1.0 ml / min.

[0065] Calibration of the GPC column set was performed with 21 polystyrene standards of narrow molecular weight distribution, the molecular weight of which ranged from 580 g / mol to 8,400,000 g / mol, and was arranged in the form of 6 "cocktail" mixtures, with at least ten times the interval between individual molecular weights. Standards were purchased from Agilent Technologies. For molecular weights equal to or greater than 1,000,000 g / mol, polystyrene standards were prepared at 0.025 g in 50 ml of solvent, and for molecular weights less than 1,000,000 g / mol, polystyrene standards were prepared at 0.05 g in 50 ml of solvent. The polystyrene standards were dissolved and gently stirred for 30 minutes at 80 degrees Celsius. Equation 1 was used to convert the polystyrene standard peak molecular weight into polyethylene molecular weight (as described in Williams and Ward, J. Polym. Sci., Polym. Let., 6,621 (1968)):

[0066] MW 聚乙烯 =A×(Mw 聚苯乙烯 ) B (Equation 3)

[0067] Where MW is the molecular weight, the value of A is 0.4315 and B is equal to 1.0.

[0068] A fifth order polynomial was used to fit the calibration points to the corresponding polyethylene equivalents.Small adjustments were made to A (approximately 0.395 to 0.440) to correct for column resolution and band broadening effects such that a linear homopolymer polyethylene standard was obtained at 120,000 g / mol Mw.

[0069] Total plate counts for the GPC column set were performed using decane (prepared as 0.04 g in 50 mL TCB). Plate counts (Equation 4) and symmetry (Equation 5) were measured at 200 microliter injections according to the following equations:

[0070]

[0071] where RV is the retention volume in milliliters, peak width is in milliliters, peak maximum is the maximum height of the peak, and 1 / 2 height is 1 / 2 the height of the peak maximum.

[0072]

[0073] Where RV is the retention volume in milliliters, and peak width is in milliliters, peak maximum is the maximum position of the peak, tenth height is 1 / 10 of the height of the peak maximum, and where post-peak refers to the tail of the peak with a retention volume later than the peak maximum, and where pre-peak refers to the front of the peak with a retention volume earlier than the peak maximum. The plate count of the chromatographic system should be greater than 24,000, and the symmetry should be between 0.98 and 1.22.

[0074] The samples were prepared semi-automatically using the PolymerChar "Instrument Control" software, where the target weight of the sample was set to 2 mg / ml, and the solvent (containing 200 ppm BHT) was added to a septum-covered vial previously sparged with nitrogen by a PolymerChar high temperature autosampler. The samples were dissolved at 160 degrees Celsius for 2 hours under "low speed" shaking.

[0075] Based on the GPC results using the internal IR5 detector (measurement channel) of the PolymerChar GPC-IR spectrometer according to Equations 6 to 8, the TM Calculations of Mn(conv), Mw(conv) and Mz(conv) were performed using the IR software, the baseline-subtracted IR chromatogram at each equally spaced data collection point (i) and the polyethylene equivalent molecular weight obtained from the narrow standard calibration curve at point (i) according to Equation 1.

[0076]

[0077] To monitor deviations over time, a flow rate marker (decane) was introduced into each sample via a micropump controlled by the PolymerChar GPC-IR system. The flow rate marker (FM) was used to linearly correct the pump flow rate (flow rate (nominal)) for each sample by comparing the RV of the corresponding decane peak in the sample (RV (FM sample)) with the RV of the decane peak in the narrow standard calibration (RV (FM calibrated)). It was then assumed that any changes in the decane marker peak time were related to linear changes in the flow rate (flow rate (effective)) throughout the run. In order to facilitate the highest accuracy in the RV measurement of the flow marker peak, a least squares fitting routine was used to fit the peak of the flow marker concentration chromatogram to a quadratic equation. The first derivative of the quadratic equation was then used to solve for the true peak position. After calibrating the system based on the flow marker peak, the effective flow rate (relative to the narrow standard calibration) was calculated as Equation 9. By PolymerChar GPCOne TM The software completes the processing of the flow marker peaks. An acceptable flow rate calibration is such that the effective flow rate should be within + / - 2% of the nominal flow rate.

[0078] Flow rate (effective) = flow rate (nominal) × (RV (FM calibrated) / RV (FM sample))

[0079] (Equation 9)

[0080] GPC deconvolution

[0081] Conventional GPC data are deconvoluted to give the most likely fit for the two molecular weight components. There are many deconvolution algorithms available both commercially and in the literature. Depending on the assumptions used, these may lead to different answers. The algorithm here is optimized for the deconvolution problem of the two most likely molecular weight distributions (plus adjustable error terms). In order to allow for changes in the underlying distribution due to small fluctuations in macromonomer binding and reactor conditions (i.e., temperature, concentration), the basis function is modified to incorporate a normal distribution term. This term allows the basis function of each component to be "smeared" to varying degrees along the molecular weight axis. The advantage is that under restrictions (low LCB, ideal concentration, and temperature control), the basis function will become a simple, most likely Flory distribution.

[0082] Three components (j=1, 2, 3) are derived, where the third component (j=3) is an adjustable error term. GPC data must be normalized and properly converted to weight fractions relative to Log 10 In other words, each potential curve used for deconvolution should be represented by a height vector h i Composition, where the height is Log 10 Molecular weights are reported at known intervals, hi The elution volume domain has been properly converted to Log 10 molecular weight domain, and h i Additionally, these data should be available in Microsoft EXCEL TM application.

[0083] Several assumptions are made in the deconvolution. Each component j consists of the most likely Flory distribution that has been extended by a normal or Gaussian function with parameter σ j The convolution is performed. The three basis functions obtained are used for Chi-square X 2 In the GPC data vector h i A minimization routine for locating the parameters of the most optimal fit to n points.

[0084]

[0085] Using Excel TM The function "NORMDIST(x, mean, standard deviation, cumulative value)" calculates the variable CumND j,k , where the parameters are set as follows:

[0086] x=μ j +(k-10)*σ j / 3

[0087] Average value = μ j

[0088] Standard Deviation = σ j

[0089] CumulativeValue = TRUE.

[0090] Table 1 below summarizes these variables and their definitions. TM The software application Solver is sufficient for this task. Constraints are added to Solver to ensure proper minimization.

[0091] Table 1: Variable definitions

[0092] Variable Name definition <![CDATA[λ j,k ]]> The reciprocal of the number average molecular weight of the most likely (Flory) distribution of component j (normal distribution slice k) <![CDATA[σ j ]]> Sigma (square root of variance) of the normal (Gaussian) spread function of component j. <![CDATA[w j ]]> Weight fraction of component j K <![CDATA[Normalization term (1.0 / Log e 10)]]> <![CDATA[M i ]]> Molecular weight of elution volume slice i <![CDATA[h i ]]> <![CDATA[log at slice i 10 (Molecular weight) height of the graph]]> n Number of slices in log molecular weight plot i Logarithmic molecular weight slice index (1 to n) j Component index (1 to 3) 1.k Normal distribution slice index <![CDATA[Δlog 10 M]]> <![CDATA[Height relative to log 10 log in the M figure 10 M i and log 10 M i-1 Average difference between]]>

[0093] The eight parameters derived from the chi-square minimization are μ1, μ2, μ3, σ1, σ2, σ3, w1, and w2. The term w3 is then derived from w1 and w2 because the sum of the three components must equal 1. Table 2 is a summary of the Solver constraints used in the EXCEL program.

[0094] Table 2: Summary of constraints

[0095] describe constraint Maximum value of fraction 1 <![CDATA[w1 < 0.95 (user adjustable)]]> Lower bound of expansion function <![CDATA[σ1,σ2,σ3>0.001 (must be positive)]]> Upper limit of extension function <![CDATA[σ1, σ2, σ3 < 0.2 (user adjustable)]]> Normalized score <![CDATA[w1+w2+w3=1.0]]>

[0096] Other constraints that should be understood include the following limitations: Only μ j > 0 is allowed, but if the Solver is properly initialized, this constraint need not be input because the Solver routine will not move any μ j to a value less than approximately 0.005. Additionally, w j should all be understood as positive. This constraint can be handled outside the Solver. If w j is understood to be generated by the selection of two points along 0.0 < P1 < P2 < 1.0; thus w1 = P1, w2 = P2 - P1, and w3 = 1.0 - P2; then the constraints on P1 and P2 are equivalent to those required for w j above.

[0097] Table 3 is an overview of the Solver settings under the Options tab.

[0098] Table 3: Solver settings

[0099] Label Value or selection Maximum time (seconds) 1000 Iteration 100 Accuracy 0.000001 tolerance(%) 5 convergence 0.001 Estimated value Tangent Derivative Forward search Newton All other options Not selected

[0100] A first guess for the values of μ1, μ2, w1, and w2 can be obtained by assuming two ideal Flory components that give the observed weight-average molecular weight, number-average molecular weight, and z-average molecular weight of the observed GPC distribution.

[0101]

[0102] w1 + w2 = 1

[0103] Then the values of μ1, μ2, w1, and w2 are calculated. Before entering the Solver for the minimization step, these parameters should be carefully adjusted to allow for a small error term w3 and to satisfy the constraints in Table II. The starting values of σ j are all set to 0.05.

[0104] Haze

[0105] Haze is measured using a Byk Haze-Gard I. After the thickness measurement, the film sample is fixed to the lens at the end of the integrating sphere of the Haze-Gard I, where it measures the Illuminant A value according to ASTM D1003. This test is performed first because it is non-destructive.

[0106] Instrumented Dart Impact (IDI)

[0107] IDI is measured according to ASTM D7192. This standard requires a probe assembly with a diameter of 12.70 mm ± 0.13 mm and a hemispherical end of the same diameter. The probe used has a 4500N range with a sensitivity of 1.1 mV / N and is designed for dynamic measurements. The dart probe assembly is mounted on top of a LinMot linear motor, which is an electromagnetic direct drive motor in tubular form. Its maximum speed is 5.4 m / s and maximum force is 1650 N.

[0108] MD and CD tearing

[0109] MD and CD tear are tested according to ASTM D1922-15 using an Elmendorf type tear tester covering the average force required to propagate a tear through a specified length of plastic film after the tear has initiated.

[0110] Example

[0111] The embodiments will be further illustrated by the following examples.

[0112] Table 4 - Process conditions for polymer examples of the present invention

[0113]

[0114]

[0115] With reference to the process conditions in Table 4 above, the above-mentioned inventive polymers were produced in a multi-reactor system. The pre-feeder reactor for producing the HMW component included a catalyst system comprising a procatalyst 1 provided as follows. The pre-feeder reactor was a tubular reactor with a stretched laminar flow distribution. The residence time in the pre-feeder was about 2 minutes.

[0116] Main Catalyst 1

[0117]

[0118] The catalyst system in the pre-feeder also included MMAO-7 (CAS 206451-54-9) co-catalyst and a deactivator in addition to the main catalyst 1. The catalyst was provided at a feed rate of about 50 g / h and included a concentration of 0.08 mmol / kg.

[0119] Reactor 2, downstream of the pre-feeder reactor, is a CSTR reactor and includes a heterogeneous Ziegler / Natta catalyst. A heterogeneous Ziegler-Natta type catalyst premix is ​​prepared substantially according to U.S. Pat. No. 4,612,300 by sequentially adding a slurry of anhydrous magnesium chloride in ISOPAR-E, a heptane solution of EtAlCl2, and a heptane solution of Ti(O-iPr)4 to a volume of ISOPAR-E to obtain a composition having a magnesium concentration of 0.20 M and a ratio of Mg / Al / Ti of 40 / 12.5 / 3. An aliquot of the composition is further diluted with ISOPAR-E to give a final concentration of Ti in the slurry of 500 ppm. Prior to being fed to and entering the polymerization reactor, the catalyst premix is ​​contacted with a dilute solution of triethylaluminum (Et3Al) at a molar ratio of Al to Ti of 4.6 to obtain an active catalyst. The Ziegler-Natta catalyst is added at a concentration of 0.63 mmol / kg.

[0120] Table 5 - Properties of polymers of the invention

[0121]

[0122] Table 6 - Properties of bulk fraction and HMW fraction

[0123]

[0124] Table 7

[0125]

[0126]

[0127] refer to Figure 4 As shown in Table 7, the HMW component increases shear thinning compared to a similar sample with an intermediate molecular weight. As described herein, an intermediate molecular weight herein corresponds to an Mw value of about 500,000 g / mol. A high molecular weight corresponds to an Mw value of 1,000,000 g / mol. Figure 4 As shown, Ref ZN (A1) without HMW components showed the lowest I 10 / I2. Further Figure 4 As shown, the slope for 5% high M (C2) is higher than that for 5% medium M (B2). Without being limited by theory, the increased slope is produced in part by shutting off the H2 feed during the polymerization to reduce termination reactions and thereby produce larger molecules.

[0128] Additionally, if Figure 5 As shown in Table 7, the HMW component provides a better balance of melt strength and shear viscosity, specifically, with low η 100(easy die flow) provides higher MS (high free surface flow stability). Figure 5 As shown, Ref ZN (A1) without HMW component exhibits the lowest melt strength. In addition, compared with similar samples with medium molecular weight, Figure 5 A clear shift of the high molecular weight samples to the upper left corner of the relevant plot is shown.

[0129] also, Fig. 6A and Figure 6B It is shown how the HMW component provides increased strain hardening for samples with the HMW component. Fig. 6A is the stress / time curve of comparative sample A1 and Figure 6B is the stress / time plot for the 5% high molecular weight sample (C1). This indicates that the molecular stress resistance is changing in nature during the orientation process. For the comparative sample without the HMW component, the slope is essentially constant over time. Fig. 6A and Figure 6B The key difference between Figure 6B A "bump" or arch in the curve. This indicates Fig. 6A Compared to the reference sample, the intramolecular bonds are enhanced due to the presence of very large linear molecules (e.g., UHMW molecules).

[0130] Single layer film manufacturing

[0131] In addition to the above-described Inventive Resins 1 and 2, films were produced from the following commercially available resins produced by Dow Inc., Midland, MI:

[0132] INNATE TM ST50 is a LLDPE resin having a density of 0.918 g / cc and a melt index (I2) of 0.85 dg / min;

[0133] AGILITY TM 1500 is a LDPE resin having a density of 0.920 g / cc and a melt index (I2) of 0.15 dg / min; and

[0134] DOWLEX TM 2045 is a LLDPE resin having a density of 0.920 g / cc and a melt index (I2) of 1.0 dg / min.

[0135] Films were produced on a Collin blown film line using the process conditions in Table 4.

[0136] Table 4

[0137] Blowing ratio (BUR) 2.5 Membrane specifications 2 mil Die clearance 80 mil Height of frost line 6 inches Output 12 lbs / hour

[0138] Table 5 Melt strength (pellet) and film data

[0139]

[0140] As shown in the above data, the tear of the inventive polymers E2 and C2 in both the CD and MD directions increased significantly by a factor of two, indicating a step change improvement in both the CD and MD directions. Without being limited by theory, this increased strength is related to the inclusion of the HMW resin in the bulk resin.

[0141] It will be apparent to those skilled in the art that various modifications and variations may be made to the embodiments described herein without departing from the essence and scope of the claimed subject matter. Therefore, this specification is intended to cover modifications and variations of the various embodiments described herein, provided that these modifications and variations fall within the scope of the appended claims and their equivalents.

Claims

1. A method of producing an ethylene-based polymer comprising a first polymer fraction and a second polymer fraction: The ethylene monomer and the optional C3-C 12 reacting an alpha-olefin comonomer in a solvent in the presence of a first catalyst in at least one initial reactor to produce the first polymer fraction reaching an outlet temperature of the reaction zone of less than 160° C., wherein the first polymer fraction has a weight average molecular weight (Mw) greater than 500,000 g / mol; The first polymer fraction, the ethylene monomer, the optional C3-C 12 introducing an alpha-olefin comonomer, the solvent, and at least one second catalyst into at least one stirred solution polymerization reactor; The ethylene monomer and the optional C3-C 12 reacting an alpha-olefin comonomer in the presence of the at least one second catalyst in the at least one stirred solution polymerization reactor to produce a second polymer fraction; and outputting an effluent from the stirred solution polymerization reactor, wherein the effluent comprises the ethylene-based polymer having the first polymer fraction and the second polymer fraction, unreacted ethylene monomer, and optionally unreacted C3-C 12 α-olefin comonomer; wherein the ethylene-based polymer comprises from 0.1 wt% to 15 wt% of the first polymer fraction and greater than 70 wt% of the second polymer fraction, and The ethylene-based polymer has a melt index (I2) of 0.1 g / 10 min to 50 g / 10 min, a density of 0.870 g / cc to 0.970 g / cc, and Mz / Mw is greater than Mw / Mn.

2. The process of claim 1, wherein the at least one initial reactor comprises at least one tubular reactor.

3. The process according to claim 2, wherein the at least one tubular reactor is a plug flow reactor.

4. The method according to any preceding claim, further comprising: The effluent of the stirred solution polymerization reactor is reacted in the presence of a third catalyst in a mixer downstream of the stirred solution polymerization reactor, wherein the third catalyst promotes the unreacted ethylene monomer and optionally any unreacted C3-C 12 Further reaction of the alpha-olefin comonomer to produce a third polymer fraction having a density and a melt index (I2) different from the second polymer fraction.

5. The method of claim 4, wherein the third catalyst comprises at least one molecular catalyst, at least one heterogeneous Ziegler-Natta catalyst, or a combination thereof.

6. The method according to any one of claims 1 to 5, further comprising: A mixer effluent from the mixer is introduced into a tubular polymerization reactor, wherein the mixer effluent comprises the ethylene-based polymer having the first polymer fraction, the second polymer fraction, and the third polymer fraction.

7. The process according to any preceding claim, wherein the stirred solution polymerization reactor comprises at least one continuous stirred tank reactor (CSTR), at least one loop reactor, or a combination thereof.

8. A method according to any preceding claim, wherein the first catalyst and the second catalyst comprise different compositions.

9. The process according to any preceding claim, wherein the stirred solution polymerization reactor comprises an outlet temperature of at least 180°C, preferably at least 190°C or most preferably at least 200°C.

10. A method according to any preceding claim, wherein the first catalyst comprises a molecular catalyst.

11. The method of any preceding claim, wherein the second catalyst comprises at least one molecular catalyst, at least one heterogeneous Ziegler-Natta catalyst, or a combination thereof.

Citation Information

Patent Citations

  • Process for preparation of homogenous random partly crystalline copolymers of ethylene with other alpha-olefins

    US3645992A

  • Ethylene polymer blend and polymerization process for preparation thereof

    US3914342A

  • Hydrocarbon interpolymer compositions

    US4076698A

  • Interpolymers of ethylene and unsaturated carboxylic acids

    US4599392A

  • Novel catalyst for producing relatively narrow molecular weight distribution olefin polymers

    US4612300A